Participation and upgrading along global value chains: the role of audit oversight - Liu, Sibo; Su, Lixin; Wu, Feng; Zhu, Xindong (Journal of International Business Studies, 2024)
We show that shared and improved auditing standards, as induced by the audit oversight arising from the Public Company Accounting Oversight Board (PCAOB)’s inspections on non-U.S. auditors, help global exporting firms upgrade themselves and tap into global value chains (GVCs). Using a dataset of U.S. waterway imports from global suppliers of 36 countries, we find that PCAOB international inspections not only lead to significantly more exports to U.S. buyers, particularly for intermediate and capital goods, but exporters also upgrade their product complexity. These results are consistent with enhanced information quality of exporters and thus reduced informational frictions with downstream importers. Echoing this notion, we find stronger GVC effects of PCAOB inspections for exporters facing more informational problems, i.e., for those with ex-ante lower reporting quality or smaller market shares, and those located in countries with weaker institutions or higher geopolitical risk with the U.S. PCAOB inspections also increase the duration length of the chain relationship and supplier firms’ relationship-specific investments in the chain. We further find that U.S. importers with a greater share of suppliers audited by PCAOB-inspected auditors exhibit boosted financial outcomes. Overall, our findings suggest that audit oversight facilitates the formation, upgrading, and performance along GVCs.